Birds of the Serra de Maracaju, Mato Grosso do Sul, Brazil - Nunes, Alessandro Pacheco; Godoi, Maurício Neves; Pivatto, Maria Antonietta Castro; Morante-Filho, José Carlos; Weffort Patrial, Eduardo; Antonio Silva, Paulo; Katherinne Stavis, Vanessa; Granville Manço, Daniel de; Barros Costacurta, Marco de; Leuchtenberger, Caroline; Lehn, Carlos Rodrigo (Revista Brasileira de Ornitologia, 2013)
The Serra de Maracaju stands out in the orography of Mato Grosso do Sul as a watershed between the Upper Paraguay and Upper Parana river basins. In this study, we report on the occurrence of 413 species of birds based on historical records and field data collected by us. The records of species such as Aburria nattereri, Ictinia mississippiensis, Spizaetus tyrannus, Micrococcyx cinereus, Berlepschia rikeri, Oxyruncus cristatus, Knipolegus lophotes, Myiarchus tuberculifer, Tyrannopsis sulphurea, Tityra semifasciata, Cyanerpes cyaneus, and Poospiza cinerea are the first for the state of Mato Grosso do Sul. The Serra de Maracaju act as an important dispersal corridor for elements of the Amazon and Atlantic Forest in the eastern border of the Pantanal. Fifteen species reported for the area are regarded as globally or nationally endangered, such Harpia harpyja, Alectrurus tricolor, and Sporophila maximiliani. Human impacting activities such as agriculture, monoculture of exotic trees, and conversion of wood into charcoal, seriously threaten the survival of these and other bird species occurring in the region. The creation of a large conservation unit and the proper management of the landscape, so as to maintain the local diversity and habitat structure, are crucial to ensure the conservation these species and, therefore, the biodiversity of the surrounding plateaus and plains of Pantanal.
Aves da Serra de Maracaju, Mato Grosso do Sul, Brasil
Keywords: Anthropogenic Effect; Avifauna; Cerrado; Conservation Management; Conservation Status; Data Acquisition; Dispersal; Endangered Species; Habitat Corridor; Historical Record; New Record; Species Conservations; Species Occurrence; Survival; Mato Grosso Do Sul; Serra De Maracaju